2018
DOI: 10.1039/c7ra12665d
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic activity of Ag/Al2O3–Gd2O3photocatalysts prepared by the sol–gel method in the degradation of 4-chlorophenol

Abstract: Ag/Al2O3–Gd2O3 showed high efficacy to photodegradate 4-chlorophenol, the strong interaction between silver nano-particles and micro-particles and Al2O3–Gd2O3 entities favors the decrease in the recombination rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 64 publications
2
22
0
Order By: Relevance
“…Qu et al previously reported that the binding energy of 367.1 eV corresponds to Ag + while those of 368.8∼369.2 eV correspond to Ag 0 at Ag 3d 5/2 of Ag 3d spectra . Our result for the main component of Ag 3d 5/2 was located at 367.2 eV, which can be assigned to Ag + ions . The Ag 3d spectra did not show peaks in the binding energy region assigned to Ag 0 (Figure S6c); i. e., metallic Ag was not observed either.…”
Section: Resultssupporting
confidence: 39%
“…Qu et al previously reported that the binding energy of 367.1 eV corresponds to Ag + while those of 368.8∼369.2 eV correspond to Ag 0 at Ag 3d 5/2 of Ag 3d spectra . Our result for the main component of Ag 3d 5/2 was located at 367.2 eV, which can be assigned to Ag + ions . The Ag 3d spectra did not show peaks in the binding energy region assigned to Ag 0 (Figure S6c); i. e., metallic Ag was not observed either.…”
Section: Resultssupporting
confidence: 39%
“…The sol-gel method was selected since this procedure allows for the simultaneous formation of metal oxides [8][9][10][11]. First, a solution with a certain amount of aluminum tri-sec-butoxide (97.0%, Aldrich, St. Louis, MO, USA) and 10 mL of 2-methylpentane 2,4-diol (99.999%, JT Baker, Phillipsburg, USA) as a complexing agent was stirred in a round glass flask for 60 min while the temperature was kept at 70 • C. Thereafter, the temperature was reduced to 50 • C and mixed with a second solution prepared by dissolving neodymium acetylacetonate (99.99%, Aldrich) in toluene (99.999%, Aldrich) at 40 • C. The resulting solution was stirred at 50 • C, then, after 60 min, 10 mL of deionized water was added dropwise to promote the hydrolysis of the aluminum and neodymium reagents to produce a gel.…”
Section: Synthesismentioning
confidence: 99%
“…According to previous reports, the modified surface can be considered a new phase with different properties associated to new surface chemistry and chemical activity [4][5][6]. We have reported that the sol-gel method is suitable to produce γ-Al 2 O 3 with photocatalytic activity to degrade organic pollutants in water [7][8][9], however it is desirable to enhance photocatalytic performance in order to reach a higher conversion in the lowest time. In earlier works, the photocatalytic activity of γ-Al 2 O 3 in the degradation of phenolic compounds has been improved by impregnating noble metal (PdO or'Ag 0 ) onto Al 2 O 3 -Ln 2 O 3 (Ln = Nd or Gd) binary oxides [8,10,11] or by doping Al 2 O 3 -Nd 2 O 3 with the semiconducting ZnO to form Al 2 O 3 -Ln 2 O 3 -ZnO ternary oxides [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, the photocatalytic activity of the Cu-CuO/ZnO composite for the degradation of phenanthrene has not yet been investigated. The amendment of the physicochemical properties of semiconductors through doping and heterostructures with rare earth metal/metal oxide for the improvement of their photocatalytic activities have been previously reported [28,29]; it is suggested that the increased photocatalytic activities of gadolinium incorporated semiconductor is mainly due to the interfacial charge transfer of its 4f shells and the elimination of electron-hole recombination. Hence, the nanocomposite (NC) of CuO/ZnO with gadolinium was considered for improved photodegradation of phenanthrene in water.…”
Section: Introductionmentioning
confidence: 99%